English resultatives a force-recipient account - Iwata, Seizi (Constructional approaches to language ;, 2020)
"The objective of this book is to develop a force-recipient account of English resultatives. Within this approach the post-verbal NP is a recipient of a verbal force, whether it is a subcategorized object or not, and the verbal force being exerted onto the post-verbal NP is responsible for bringing about the change as specified by the result phrase. It is shown that many apparent puzzles posed by English resultatives are due to the complex interplay between the verb meaning and the constructional meaning, or between the verb meaning and the semantics of the result phrase. Thus the proposed account can provide answers to the question "Which resultatives are possible and which are not?" in a coherent way. Also, the proposed account reveals that English resultatives are not a monolithic phenomenon, and that some "resultatives" cited in the literature as such are not resultatives at all. This book is of interest not only to practitioners of Construction Grammar but also to everyone interested in English resultatives"--